Impact of Parkinson's Disease-Related Dysphagia Severity on Quality of Life: Comparison Between Self-Reports and Videofluoroscopic Swallowing Study Results - Serkan Bengisu; Merve Savaş; Demet Aygün; Senanur Kahraman Beğen; Tutku Altıntaş; Burak Manay (The Turkish Journal of Ear Nose and Throat)
Objective: The aim of this study was to evaluate the impact of dysphagia due to Parkinson's disease (PD) on quality of life and to compare the results of the objective assessment with those of patient self-reports.Materials and Methods: The study included 28 participants with PD. Patients were assessed clinically using the Eating Assessment Tool (EAT-10) and objectively via video-fluoroscopy (VFSS). The data obtained with VFSS were scored using the Penetration Aspiration Scale (PAS) and Functional Oral Intake Scale (FOIS) by an SLP blinded to patient information and clinical assessment methods. Swallowing disorder-related quality of life was assessed using the Swallowing Quality of Life Questionnaire (SWAL-QOL).Results:It was found that as PD severity and duration increase, the severity of swallowing impairment also increases, leading to a negative effect on quality of life being affected negatively accordingly (p<0.05). According to the SWAL-QOL questionnaire results, dysphagic patients had lower SWAL-QOL scores, particularly in terms of burden, eating desire, duration, symptom frequency, food selection, and mental health domains. In addition, a statistically significant difference was found between the groups with and without dysphagia in all EAT-10, PAS, and FOIS scores (p=0.000, p=0.20, p= 011). There was no statistically significant difference between self-reports on the presence of swallowing disorders and the results of the objective assessment using the VFSS (p=0.298).Conclusion:In patients with PD, swallowing impairment becomes more pronounced as the duration and severity of the disease increase, and quality of life is negatively affected. The results of this study suggest that the results between objective assessments and patient reports are inconsistent and therefore emphasise the importance of objective measurement methods in dysphagia assessment.